Is tourism and hospitality education supporting sustainability? - Berjozkina, Galina; Melanthiou, Yioula (My University, 2021)
Purpose: Education can provide learners with the necessary awareness, values and skills to understand the complexity of sustainability. This study aims to analyse the extent to which sustainability concepts have been implemented in higher education programmes in the tourism and hospitality fields. Design/methodology/approach: For the purpose of the current study, data on all tourism and hospitality programmes offered in Cyprus higher education institutions (HEIs) at the Bachelor level was obtained. Analysis was conducted on publicly available programme descriptions, learning outcomes, program content and syllabi and course descriptions. Findings: The study finds that sustainability concept implementation in undergraduate hospitality and tourism degree programmes is at a developing stage. The majority of the HEI follow trends and offer sustainability courses either as compulsory or elective courses, but concept implementation in programme learning outcomes and programme descriptions is relatively limited. Originality/value: This paper presents a review of data and evidence on sustainability concept implementation in tourism and hospitality education in Cyprus.
Keywords: Education; Hospitality; Tourism; Sustainability; Sustainable tourism